The vital minimum in the Mexican tax constitutionalism - Lerma Charles, Marlon Alejandro (Universidad Autónoma de Tamaulipas, 2021)
The vital minimum has been defined by the Supreme Court of Justice of the Nation, as a guarantee based on freedom, solidarity, material equality, the social rule of law and human dignity, considering that every person, to fully enjoy their freedoms, requires a minimum of economic security to be able to satisfy their basic needs. From this it is noted that the guarantee referred is necessarily only protective of natural and non-legal persons, and this is due to its own nature, since it encompasses the positive or negative measures that the State must adopt to avoid that a person is unconstitutionally reduced in his value as a human being because he does not have all those material conditions that provide him with a dignified existence, so that such a situation could not be logically or legally possible in a legal entity. This guarantee has permeated in various areas of the human being, from the labor, social security, family, even administrative and fiscal aspects. The purpose of the work will show the origin of the guarantee of the vital minimum in the Mexican tax regulations, as well as the current jurisdictional criteria on it.